Zbycie udziałów w spółce z o.o. objętych wspólnością majątkową małżeńską - Szermach, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
There is no doubt that in business practice one rather frequently comes across shares in a limited liability company which are subject to marital community property. In spite of its popularity, the subject matter gives rise to numerous controversies, as reflected in the diversity of views expressed in the doctrine and in positions of judicature. The said issue goes beyond the frames of one legal domain, considering the fact that what applies here are the provisions of the Polish Family and Guardianship Code and the Polish Commercial Companies Code. Even though both regulations are incompatible, it does not appear possible to completely separate the legal and family relationships from the commercial companies relationships in case a spouse disposes of shares which are subject to marital community property.
Keywords: spółka z ograniczoną odpowiedzialnością; zbycie udziałów; wspólność majątkowa; małżeństwo; kodeks spółek handlowych; kodeks rodzinny i opiekuńczy